Consent Issues in the Management of Acute Ischemic Stroke: AAN Position Statement. (11th January 2022) - Sattin, Justin A.; Chiong, Winston; Bonnie, Richard J.; Kirschen, Matthew P.; Russell, James A.; ,
Abstract : This position statement briefly reviews the principle of informed consent, the elements of decisional capacity, and how acute stroke may affect this capacity. It further reviews the role of surrogate decision-making, including advance directives, next of kin, physician orders for life-sustaining treatment, and guardianship. In some cases of acute stroke in which the patient lacks decisional capacity and no advance directives or surrogates are available, consent to treatment may be presumed. The document describes the rationale for this position and various considerations regarding its application to IV thrombolysis, neuroendovascular intervention, decompressive craniectomy, and pediatric stroke. The document also reviews consent issues in acute stroke research.